FAKTOR-FAKTOR YANG MEMPENGARUHI RENDAHNYA MINAT BACA MASYARAKAT PADA PERPUSTAKAAN DESA INSAN KAMIL DI DESA MUARA UWAI KECAMATAN BANGKINANG KABUPATEN KAMPAR - Israhainy, Tika; Maemunaty, Titi; Jas, Jasfar (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: Research it is based on the state of factors affecting the low reading interest. Because factors affecting the low reading interest form a reference development the factors that affects the low reading interest in the society in the library village insan kamil in desa muara uwai kecamatan bangkinang kabupaten kampar. Formulation problems this research is will the most dominant factors to influence the low reading interest in the society in the library village insan kamil in desa muara uwai kecamatan bangkinang kabupaten kampar?. The purpose of this research is to find factors the most dominant to influence the low reading interest in the society in the library village insan kamil in desa muara uwai kecamatan bangkinang kabupaten kampar. Population in this study 200 people. So research sample areas 115 people and 30 people sample test on critical level 10 %, sample used is sampling incidental. An instrument data collection that is chief with 46 a statement and if the trial live 42 a statement valid for in made instrument research. Data analysis through descriptive analysis quantitative. The outcome of research on the four indicators of a conclusion can be drawn that factors the existence and kejangkauan reading materials and these that make reading interest low, than another factor .It means children assume that instrument supporting in the library inadequate, so that the community reluctant to go library.Key words: Reading Interest, Factors That Affects The Low Reading Interest